أثر لغة الإعلام على لغة التداول - خلفاوي, فريد (جامعة الوادي - University of Eloued, 2020)
ملخص: تتناول هذه الدراسة قضية هامة من قضايا البحث اللغوي العام، إذ تتعرض إلى أهم العلاقات الحاصلة بين اللغة والمجتمع باعتبار اللغة أحد أهم الركائز التي يقوم عليها المجتمع نشأة وصيرورة وتطورا. فاللغة باعتبارها الوسيلة الأهم في قيام المجتمعات واستوائها واستقرارها وأمدها، وهي العنصر الذي يدخل في نشأة كل العناصر المشكلة لهذه المجتمعات، بل تبقى ملازمة لها، لأن تلك العناصر -مهما كانت- لا يمكنها بأي حال أن تستغني عن اللغة استغناءً كليا، من هنا حصلت علاقات هامة بينها، فظهور العلوم والمعارف المختلفة بشكل عام يظهر ويتطور ويستمر عبر اللغة، وينقل من جيل إلى جيل بواسطتها. وسنبين خلال هذا المقال الدور الذي تؤديه اللغة الإعلامية بشكل عام في شحن اللغة المتداولة داخل المجتمع والتأثير فيها، حيث إن دورها لا يقتصر على نقل الأخبار والأحداث فحسب؛ إنما يتعدى إلى عمق لغة المجتمع، فتتدخل حتى في تكوينها وفي تطورها. الكلمات المفتاحية: لغة الإعلام؛ اللغة المتداولة؛ الأثر؛ الإيحاء؛ التضمين؛ المجاز. Abstract: This study deals with an important issue of general linguistic research, It expose to the most important relationships between language and society, Considering that language is one of the most important support, On which society is based, Foundation, continuation and development. Language is the most important tool, In equalization, stabilization, and maybe duration of societies, And it is the element that enters in composition of all the elements that constitute these societies, but it stay Inherent to her, Because those elements, whatever they are It cannot in any way To dispense with language a Complete dispense, From here, there were an important relations between them, The Appearance of different sciences and knowledge generally Appears, develops and continues through language, and transmitted from one generation to the next through it. We will explain through this article, The role of the media language In general, the charge of the spoken language within the community, And its influence on it, As its role is not limited to the transfer of news and events only, but It goes beyond the depth of language society, It interferes even in its Foundation and development. key words; Media language - The spoken language – Impact - inspiration – inclusion – Metaphor.
مقال
Keywords: لغة الإعلام ; اللغة المتداولة ; الأثر ; الإيحاء ; التضمين ; المجاز